Relationship between Anxiety and Quality of Life in Nurses Caring for Covid-19 Patients in Different Wards - Seyvan Sobhani; Isa Mohammadi Zeidi; Sara Tabanfar; Mohammad Sharif Hosseini (Muhandisī-i bihdāsht-i ḥirfah/ī, 2022)
Background and Objective: Nurses are at high risk of contracting Covid-19 due to their occupational nature. Therefore, the present study aimed to determine the relationship between anxiety and quality of life among nurses caring for Covid-19 Patients in different wards. Materials and Methods: A total of 142 nurses working in Covid-19 wards of hospitals affiliated to Qazvin University of Medical Sciences were selected via multi-stage random sampling and participated in this descriptive cross-sectional study. Data were collected using the demographic information questionnaire, Corona Disease Anxiety Scale (CDAS), and quality of life questionnaire (SF-36). Results: The mean age of participants was 31.37±6.1 years, and the majority of nurses (62%) were married. The mean scores of Covid-19 anxiety and quality of life were reported as 18.70±8.79 and 55.57±18.70, respectively. The anxiety score was assessed as moderate. The highest and lowest quality of life scores belonged to the physical function (69.04±29.03) and role-emotional dimensions (48.35±42.86), respectively. There was a significant negative correlation between anxiety and quality of life (P<0.001; r= -0.350). Nurses working in emergency and general wards had the highest and lowest scores of anxiety (P=0.032), respectively. Nurses working in general and coronary care unit (CCU)  wards had the highest and lowest scores of quality of life (P=0.005), respectively, compared to other groups. Conclusion: As evidenced by the obtained results, nurses working in Covid-19 wards are exposed to moderate levels of anxiety. Health managers are suggested to identify and eliminate the causes of anxiety in nurses in an attempt to improve their quality of life by establishing counseling and specialized training centers for nurses.